INNV-16. CLINICAL APPLICABILITY OF INDIVIDUALIZED DRUG RESPONSE PROFILING UTILIZING EX-VIVO TISSUE-DERIVED 3D CELL CULTURE ASSAYS IN HIGH-GRADE GLIOMA: A SINGLE INSTITUTION CASE SERIES USING 3D-PREDICT RESULTS. (9th November 2020) - Lipinski, Lindsay; Abad, Ajay; Mechtler, Laszlo; Fabiano, Andrew; Smith, Ashley; DesRochers, Teresa; Gevaert, Matthew; Vibat, Cecile Rose; Fenstermaker, Robert
Abstract: Recurrent high-grade glioma is a challenging disease process, without consensus on effective second-line therapy options. Individualized, patient-specific, biologically-based data is desirable in driving therapeutic decision-making. Patients with recurrent high-grade glioma and planned surgical re-resection at our institution were prospectively enrolled into the 3D-PREDICT study. Tissue was collected at the time of surgery for ex vivo 3D cell culture assays comprising a panel of agents commonly used for high-grade glioma, including chemotherapies and targeted therapies used in other solid cancers. In all cases, therapeutic agent selection was guided by the neuro-oncologist's clinical judgement, factoring the patient's age, performance status, comorbidities, toxicities/side effect profile of potential agents, and drug accessibility, plus ex-vivo drug response RESULTS: We present 3 cases in which the selection of agents was influenced by the tissue-derived 3D cell culture results; treatment led to clinical response observed in terms of progression free survival, quality of life, and pharmacologic tolerability. In Case 1, a patient with recurrent anaplastic astrocytoma was treated with a BRAF inhibitor for 12 months with excellent tolerability and no radiographic progression. Case 2 demonstrates the use of combination bevacizumab and irinotecan after disease progression subsequent to standard treatment. This patient had local radiographic control for 7 months, tolerating the regimen well. In Case 3, an individual with recurrent glioblastoma was treated with combination carboplatin and etoposide based on assay response prediction to both agents; treatment has been tolerated well with radiographic stability at 6 months while maintaining good performance status. This case series represents our institutional experience of utilizing patient-specific, ex-vivo tissue-derived cell drug response profiling to guide choice of therapy for recurrent high-grade glioma patients. Using individualized, tumor-specific drug sensitivity data to guide these decisions is representative of the ongoing paradigm shift into the realm of individualized medicine to improve outcomes in cancer patients.